(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes physiological approaches to enhancing the adaptive reserves of the human organism. The study examines the concept of adaptive reserves, the organism’s capacity to adjust to external and internal stressors, and the adaptive mechanisms underlying the functioning of physiological systems. Key physiological pathways for increasing adaptive reserves are identified, including physical exercise, breathing techniques, healthy nutrition, immune strengthening, and psychological stability. In addition, the paper provides scientific justification that improving adaptive reserves enhances fatigue resistance, work capacity, and overall health.